2021
DOI: 10.3389/fcvm.2020.619612
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Deregulation and Emerging Role of Phosphatases in Diabetic Peripheral Artery Disease

Abstract: Peripheral artery disease is caused by atherosclerosis of lower extremity arteries leading to the loss of blood perfusion and subsequent critical ischemia. The presence of diabetes mellitus is an important risk factor that greatly increases the incidence, the progression and the severity of the disease. In addition to accelerated disease progression, diabetic patients are also more susceptible to develop serious impairment of their walking abilities through an increased risk of lower limb amputation. Hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 134 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…Many of these metabolic alterations have been largely associated with insulin resistance and DM [ 77 , 78 , 79 ]. It is well known that DM greatly increases the incidence, progression, and severity of CLI [ 80 ]. Hyperglycemia affects the development of collateral arteries in response to ischemia and it also promotes down-regulation of proangiogenic factors together with impaired initiation of vascular angiogenesis [ 80 ], endothelial dysfunction, or higher inflammatory progression [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these metabolic alterations have been largely associated with insulin resistance and DM [ 77 , 78 , 79 ]. It is well known that DM greatly increases the incidence, progression, and severity of CLI [ 80 ]. Hyperglycemia affects the development of collateral arteries in response to ischemia and it also promotes down-regulation of proangiogenic factors together with impaired initiation of vascular angiogenesis [ 80 ], endothelial dysfunction, or higher inflammatory progression [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that DM greatly increases the incidence, progression, and severity of CLI [ 80 ]. Hyperglycemia affects the development of collateral arteries in response to ischemia and it also promotes down-regulation of proangiogenic factors together with impaired initiation of vascular angiogenesis [ 80 ], endothelial dysfunction, or higher inflammatory progression [ 81 , 82 , 83 , 84 ]. Furthermore, diabetic patients show dysfunctional CACs [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTPs have progressively emerged as potent players in growth factor unresponsiveness in vascular cells leading to the progression of several vascular complications of diabetes. 17 Previous studies have reported that hyperglycemia-induced modification of PTP expression or activity has been shown to deregulate the insulin, PDGFR-β, and VEGFR2 pathways contributing to nephropathy, 18 retinopathy, 16 or PAD. 19…”
mentioning
confidence: 99%
“…Thus, a potential regulatory mechanism was absent in diabetics. Angiogenesis in diabetic PAD patients is impaired due to hyperglycemia [ 26 , 27 ]. In contrast, hypoglycemia is an inducer of the angiogenic switch [ 13 ].…”
Section: Discussionmentioning
confidence: 99%